Optimum Design Research on the Link Mechanism of the JP72 Lifting Jet Fire Truck Boom System - Guo Tong; Wang Jiawen; Liang Yingnan; Peng Buyu; Liu Tao; Liu Yiqun (Jixie chuandong)
The boom link mechanism refers to the key mechanism used to connect the boom and the body, which has an important impact on the stability, safety and efficiency of the elevating jet fire truck. Through mathematical models and computer simulations, it is the current mainstream optimization direction to optimize the structure of the boom linkage mechanism and improve its strength and stability. The finite element analysis method was used to establish a mathematical model, and the optimization goal was to minimize the sum of the forces on the hydraulic cylinder, which was transformed into a mathematical programming problem. The initial value, which was obtained in the finite element analysis, was difficult to meet all the design requirements, so the research focus transformed into solving optimization problems, which need to gradually optimize through iterations. The fmincon function was used to realize the sequential quadratic programming (SQP) algorithm, which is one of the most effective methods to solve the constrained nonlinear optimization problems, for the optimal design. After several iterations of calculation and optimization design, the design scheme that met the work requirements was successfully obtained.